2019
DOI: 10.1021/acs.organomet.9b00586
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of H+/H/H/e Transfer from [CpV(CO)3H]: Comparisons to the Isoelectronic CpCr(CO)3H

Abstract: Hydrogen atom (H•) donors generated from H2 facilitate the atom efficient reduction of small molecule substrates. However, generating H• donors with X–H bond dissociation free energies (BDFEs) below 52 kcal mol–1 is especially challenging because they thermodynamically favor the bimolecular evolution of H2. We have recently proposed that [CpV­(CO)3H]− catalyzes the conversion of H2 into a proton, an electron, and a hydrogen atom in the presence of a sacrificial base. In order to understand the driving force fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…WF reactions oen require an oxidant, such as TBHP or O 2 , consistent with the requirement for higher oxidation states. Second, the SF hydrides are supported by strong-eld CO and phosphine ligands, giving a low-spin electronic conguration, while the WF metal hydrides for catalytic HAT 23 These studies indicate that manipulating the oxidation states and redox potentials of MHAT catalysts (both SF and WF) is a promising area for continued study. It is likely that modication of the geometry will also be inuential because this changes the relative energies of different spin states and oxidation states.…”
Section: Properties Of Metal Hydrides In Mhat Reactionsmentioning
confidence: 94%
See 2 more Smart Citations
“…WF reactions oen require an oxidant, such as TBHP or O 2 , consistent with the requirement for higher oxidation states. Second, the SF hydrides are supported by strong-eld CO and phosphine ligands, giving a low-spin electronic conguration, while the WF metal hydrides for catalytic HAT 23 These studies indicate that manipulating the oxidation states and redox potentials of MHAT catalysts (both SF and WF) is a promising area for continued study. It is likely that modication of the geometry will also be inuential because this changes the relative energies of different spin states and oxidation states.…”
Section: Properties Of Metal Hydrides In Mhat Reactionsmentioning
confidence: 94%
“…A recent experimental study in a SF system showed the complementary trend, that the oxidation from vanadium( i ) [CpV(CO) 3 H] – to vanadium( ii ) CpV(CO) 3 H decreases the V–H BDE from 55 to 36 kcal mol –1 . 23 These studies indicate that manipulating the oxidation states and redox potentials of MHAT catalysts (both SF and WF) is a promising area for continued study. It is likely that modification of the geometry will also be influential because this changes the relative energies of different spin states and oxidation states.…”
Section: Metal Hydrides In Mhat Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, VH­(Cp)­(CO) 3 , which is produced by oxidation of the anion [VH­(Cp)­(CO) 3 ] − is proposed to be completely unstable because it is rapidly trapped by MeCN to produce VHCp­(CO) 3 (MeCN) with a very weak V–H bond (BDFE 36.1). Therefore, it evolves H 2 as in eq . The oxidation of a dihydride or polyhydride complex might result in the intramolecular formation of an H–H bond to generate a dihydrogen ligand ,, as first proposed in the oxidation of ReH 7 (PPh 3 ) 2 .…”
Section: Introductionmentioning
confidence: 97%
“…Elaborate wave function theory methods such as CCSD­(T) typically yield high accuracy for electronic energies but are not computationally feasible for larger molecules or in extensive screening studies. , Density functional theory (DFT)-based methods, however, can be routinely applied for systems with a few hundred atoms and offer a good compromise between the computational cost and accuracy. There are many examples of DFT computations of redox potentials for organic , and organometallic compounds. Combined WFT/DFT schemes such as the connectivity-based hierarchy (CBH-Redox) model by Raghavachari et al provide cost-effective alternatives to DFT.…”
Section: Introductionmentioning
confidence: 99%